Analysis of the marine resource environmental carrying capacity in Zhejiang Province based on the Pressure-Support and Destructiveness-Resilience and Degradation-Promotion (PS-DR-DP) model - Ying, Chao; Yang, Yunze; Liu, Yongchao (Frontiers in Marine Science, 2022)
Introduction Large-scale and high-intensity marine resource exploitation activities have brought irreversible influences on the marine resource environment and ecosystem. As an important index to evaluate the state of marine development, the marine resource environmental carrying capacity (MRECC) is vital to the sustainable development of the sea areas. Methods In this study, an evaluation index system was established based on the PS-DR-DP (Pressure and Support-Destructiveness and Resilience- Degradation and Promotion) theoretical model. The MRECC in Zhejiang Province from 2004 to 2018 was evaluated through the categorical arrangement polygon representation. Moreover, the coordination degree of the MRECC system was analyzed by using the coupling harmonious degree model. Results and Discussion Results demonstrated the following from 2004 to 2018: 1) The MRECC level in Zhejiang Province increased firstly, then decreased slightly, and finally presented a slow increasing trend. 2) The mean contributions of the acting forces in the MRECC system in Zhejiang Province fluctuate between 0.64 and 0.68. It was in the high-speed unsteady growth and tended to be the ideal carrying state. The positive force tends to increase, while the negative force is generally stable or only slightly increased except for the degradation force. 3) The coupling degree and degree of coupling coordination of the acting force subsystems in the marine resource environmental system in Zhejiang Province presented a rising trend. The coupling degree ranged between 0.50 and 0.80 except for those in 2004, 2006, and 2007. The acting force subsystems in the marine resource environmental system in Zhejiang Province were generally running-in during the study period. The coupling degree type changed from mild imbalance to moderate coordination.